2012
DOI: 10.1093/rheumatology/kes269
|View full text |Cite
|
Sign up to set email alerts
|

Is serum urate causally associated with incident cardiovascular disease?

Abstract: Serum urate is likely to be causally associated with CVD. This supports public health action to reduce urate levels in populations with significant burdens of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…28 Thus, hyperuricemia apparently predicts CVD, but it has thus far not been established as a causal cardiovascular risk factor. [29][30][31] In the LURIC study, the UA concentration was associated with a number of pathologic conditions. By contrast, CORs were not significant for any of these conditions when calculated using the GRS derived from SNPs associated with UA concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Thus, hyperuricemia apparently predicts CVD, but it has thus far not been established as a causal cardiovascular risk factor. [29][30][31] In the LURIC study, the UA concentration was associated with a number of pathologic conditions. By contrast, CORs were not significant for any of these conditions when calculated using the GRS derived from SNPs associated with UA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…24 Because this study only used one SNP in the SLC2A9 gene as an instrumental variable, we also calculated CORs and CHRs using a single SNP in SLC2A9 (rs12498742), which is in high linkage disequilibrium with the one used by Palmer et al The COR for prevalent CAD was not significant (data not shown) and estimates for fatal events derived from this analysis were very similar compared with the results obtained for GRS 8 (Supplemental Table 6), which is expected because the SLC2A9 SNP shows by far the strongest association with UA. Regarding all-cause mortality and cardiovascular mortality, most studies find that serum UA is an independent predictor of cardiovascular end points, especially in patients with CAD, 17,30,[33][34][35] but some studies reported the opposite. 29,36,37 Possible explanations for diverging results could be sex-specific effects, 38 an interaction with kidney function, 39 or the possibility that UA might turn pro-oxidant under certain conditions (e.g., CAD).…”
Section: Discussionmentioning
confidence: 99%
“…Most existing evidence was in older adults already at higher CVD risk (i.e., greater disorders in classic CVD risk factors, such as body mass index (BMI)) [ 8 ],[ 9 ]. Elevated sUA concentration appeared to be a circulating marker for classic CVD risk factors in some studies [ 2 ], while others inferred a possible causal association between sUA and CVD events [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that hyperuricemia is associated with increased mortality, cardiovascular morbidity, and renal impairment. 1,2 On the other hand, elevated uric acid levels seem to be essential for higher cognitive development in humans when compared with other mammals. 3,4 Thus, the definite role of elevated uric acid levels in the clinical setting except from gout seems to be an open question.…”
mentioning
confidence: 99%